CARE PATTERN BASED ON THE LEARNING OF ADULTS (ANDRAGOGI) TO STUDENTS OF DIRECTORS IN BINTARA POLICE SPN CISARUA POLDA JABAR - Sopyandi, Sobana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The background of this research is that it is not easy to create a Bintara Police student from civil society to become a member of the National Police. The backgrounds of students who come from a variety of characters and different educational backgrounds become obstacles in forming non-commissioned police officers, especially students who have just graduated from high school with their thoughts still playing and free. The purpose of this study was to determine how the pattern of adult learning-based parenting (Andragogy) to students of the West Java Police of the West Java Police National Education Department.Theories used in this study are the theory of parenting, the theory of formation of the National Police Force and the theory of adult education.Researchers used interview and observation techniques with qualitative descriptive methods to obtain information from informants. The sample in this study was a Cisarua SPN school principal, one student escort and three Cisarua SPN student representatives.The results of the study at the West Java Regional Police Cisarua SPN are going well so that the results obtained from the learning process are a member of the National Police who can serve, protect and protect the community. These results are inseparable from the role of a student companion in the implementation of the learning process or care provided during the prospective Police member training.The conclusion of the research at the Cisarua SPN is the role of a student escort or Danton, who becomes a student facilitator, the facilitator carries out his duties in accordance with the principles, assumptions of adult education and also as a caregiver for students who pay attention to their role as caregivers.